If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -1n = 10 Solving 17 + -1n = 10 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -1n = 10 + -17 Combine like terms: 17 + -17 = 0 0 + -1n = 10 + -17 -1n = 10 + -17 Combine like terms: 10 + -17 = -7 -1n = -7 Divide each side by '-1'. n = 7 Simplifying n = 7
| (c+4)(2c+7)= | | 6x-12=9x+15 | | A=11x+kx | | 15x=13x+12 | | 4v=40 | | 10x+24=Xb+ax+ab | | log(6)(6x-1)=1 | | 3(2x+6)=4x-8 | | z=2z+3z | | 252=45t | | 0.15x+3.45=46.5 | | -2(4n+4)=6 | | H=35t-16t^2 | | -3y+8=9 | | 15*3n= | | -1/7t9 | | 5(5x-2)=15 | | 4-9/5x5 | | 1.5x=16 | | P=2(62)+2(65) | | 4x-2z=3y | | 5d-(-3)=53 | | 8x+7-y=38 | | y=9x^2+18*x-6 | | 5p+(3p-20)=180 | | 7=x/2-5 | | 5d-(-3)=52 | | -x-23=5x | | 93=16-5x | | (10x-4)(x+1)=0 | | -4(v-2)=-6n+34 | | 2(4w+10)*3=6 |